(untitled) (Revista de Ciências Agroveterinárias, 2023)
Soil fertility problem is a major constraint to faba bean production in Wolaita Zone in Ethiopia. Hence, a field experiment was conducted in Kokate Marachare sub-district during 2019 and 2020 cropping seasons to determine the optimum N, P, and K fertilizers for enhanced uptake and use efficiency of faba bean. Three rates of N (0, 23, and 46 kg N ha–1), P (0, 46, and 92 kg P2O5 ha–1), and K fertilizer (0, 30, and 60 kg K2O ha–1) were tested using RCBD with three replications. Data on agronomic efficiency (AE), agro-physiological efficiency (APE), apparent recovery efficiency (ARE), and utilization efficiency of N, P, and K nutrients were analyzed. The results revealed N, P, and K uptake efficiency (UE) indices of faba bean were significantly influenced by the main effects of the rate of nitrogen, phosphorus, and potassium fertilizers. Thus, applying 23 kg N ha–1, 46 kg P2O5 ha–1, and 30 kg K2O ha–1 resulted higher N, P, and K AE, respectively (33.70 kg kg-1, 13.43 kg kg-1, and 27.32 kg kg-1); PE (76.87 kg kg-1, 104.51 kg kg-1, and 118.83 kg kg-1); APE (40.49 kg kg-1, 104.51 kg kg-1, and 68.07 kg kg-1); ARE (84.48%, 2.00%, and 40.30%); and UE (63.47 kg kg-1, 2.52 kg kg-1, and 56.08 kg kg-1). Therefore, 23 kg N ha–1, 46 kg P2O 5ha–1, and 30 kg K2O ha–1 are recommended for the higher N, P, and K uptake and use efficiency of faba bean.